Cigarette butt littering in city streets: a new methodology for studying and results. Issue 1 (20th July 2012) - Patel, Vimal; Thomson, George W; Wilson, Nick
Abstract : Objectives: The objectives of the present work were to (a) develop a relatively simple single-observer method for data collection on cigarette butt discarding; and (b) quantify cigarette butt discarding behaviour in city streets. Methods: A method was developed, piloted and refined (with interobserver assessment). Cigarette butt discarding was systematically observed by a single data collector while walking a continuous circuit of busy downtown streets in a capital city (Wellington, New Zealand). Results: The final method appeared feasible in this setting and seemed efficient (at 5.5 discarding events observed per hour). A clear majority (76.7%; 95% CI 70.8 to 82.0%) of the 219 smokers observed littered their cigarette butts. Butt littering was more common for those who did not extinguish their cigarette (94.4% vs 4.5%, p=0.003). Butt littering was more common in the evening versus lunchtime periods of observation (85.8% vs 68.1%, p=0.002, logistic regression analysis). Overall, most smokers (73.5%) did not extinguish their butts and some placed lit butts in bins (constituting a risk of bin fires). The context for this littering was a high density of rubbish bins on this circuit with a mean of 3.5 bins being in view and with a bin every 24 m on average. Conclusions: Butt littering behaviour appears to be the norm among smokers in this urban setting, even though rubbish bins were ubiquitous. One solution is stronger enforcement of littering laws. Nevertheless, in a society with a national smokefree goal (by year 2025 for New Zealand), it would probably be more logical and cost effective to move to smokefree policies for major city streets, which are used in a number of jurisdictions internationally.